Biotinidase Deficiency and Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Preliminary experiences with screening of 24,300 newborns detected 1 infant with biotinidase deficiency at the Depts of Paediatrics, Univ of Verona, Policlinic Borgo Roma, Verona, Italy, and the Hosp for Sick Children, Toronto, Canada.